OPPORTUNITIES FOR APPLICATION OF THE PROBIOTIC MEDICATIONS AMONG CHILDREN - A.A. Alekseeva; E.A. Vishneva (Педиатрическая фармакология, 2008)
The article provides the data on the new application and effectiveness aspects of the probiotics from the viewpoint of the evidence based medicine. It demonstrated the decrease of the chronic nasopharynx pathology backsets in the event of probiotic prescriptions. The authors highlight the results of the research, in which the given medications were successful applied to prevent the antibiotic associated diarrhea among the children, suffering from the respiratory diseases.Key words: probiotics, lactobacillus, bifidobakterium, intestinal dysbiosis, children.